The Structural, Biological, and In-Silico Profiling of Novel Capryloyl Tetra-Glucoside and Aliphatic Ester Constituents from the Abutilon indicum Offers New Perspectives on the Treatment of Pain and Inflammation - Shadma Wahab; Abdulrhman Alsayari; Abdullatif Bin Muhsinah; Dalia Almaghaslah; Anzarul Haque; Mohammad Khalid; Sulaiman Mohammed Alnasser; Faizul Azam; Md. Sarfaraj Hussain (Plants, 2022)
Abutilon indicum L. (Malvaceae), more often referred to as Peeli booti, Kanghi, and Kakhi, is a perennial shrub found in many countries of Asia. Traditionally, this plant is used as a diuretic to treat inflammation, discomfort, urethral infections, and gout. Inflammation and pain are key topics of interest for researchers throughout the globe, since they are linked to almost every illness that could affect humans or animals. The present study was conducted to isolate the phytoconstituents from the methanolic extract of Abutilon indicum collected from the Bihar state Koshi river belt in India, and to evaluate the isolated phytoconstituents’ ability to reduce nociception and inflammation. Furthermore, molecular docking was performed to investigate the molecular interaction profile, with possible therapeutic targets for anti-inflammatory medicines. A. indicum methanolic extract yielded two novel phytocompounds identified as 5′-hydroxyhexyl n-hexadecanoate (AB-01) and n-octanoyl-β-D-glucopyranosyl-(2′-1′′)-β-D-glucopyranosyl-(2′′-1′′′)-β-D-glucopyranosyl-(2′′′-1′′′′)-β-D-glucopyranoside (AB-05), together with three previously recognized phytocompounds such as ester glucoside. All isolated molecules were tested for the efficacy of analgesic and anti-inflammatory characteristics at doses of 5 and 10 mg/kg body weight. The isolated compound’s molecular interaction profile with anti-inflammatory drug targets cyclooxygenase-2 and tumor necrosis factor-alpha possessed high potential energy in molecular docking. These findings may aid in developing anti-inflammatory and analgesic drugs from A. indicum.